TIF2, a 160 kDa transcriptional mediator for the ligand-dependent activation function AF-2 of nuclear receptors. - Voegel, J J (1996)
Nuclear receptors (NRs) act as ligand-inducible transcription factors which regulate the expression of target genes upon binding to cognate response elements. The ligand-dependent activity of the NR activation function AF-2 is believed to be mediated to the transcription machinery through transcriptional mediators/intermediary factors (TIFs). We report here the cloning of the 160 kDa human nuclear protein TIF2, which exhibits all properties expected for a mediator of AF-2: (i) it interacts in vivo with NRs in an agonist-dependent manner; (ii) it binds directly to the ligand-binding domains (LBDs) of NRs in an agonist- and AF-2-integrity-dependent manner in vitro; (iii) it harbours an autonomous transcriptional activation function; (iv) it relieves nuclear receptor autosquelching; and (v) it enhances the activity of some nuclear receptor AF-2s when overexpressed in mammalian cells. TIF2 exhibits partial sequence homology with the recently isolated steroid receptor coactivator SRC-1, indicating the existence of a novel gene family of nuclear receptor transcriptional mediators.